RELIGION AND UNIFORM CIVIL CODE - Kadankavil, Thomas (Journal of Dharma, 1986)
Non-interference in the religious matters of their subjects was the general policy followed by the British rulers in India. Each religious community was permitted to follow its personal laws in the field especially of marriage, divorce, inheritance, succession, gifts and adoption of children. This was a tradition the British inherited from the Mughal period during which although the Civil Laws and the Criminal Laws in force were the Islamic Law, non-Muslims had the freedom to follow their own religious and customary laws. When the East India Company re-organized the Judiciary in 1765, it left the Islamic Law intact, but in 1862 the Islamic Criminal Law was replaced by the Indian Penal Code which still continues to be in force under the same name. But as regards the laws governing the family and personal matters, in compliance with the demand of Muslims in general the ’Muslim Personal Law (Shariat) application Act of 1937, was enacted. Under this act it was provided that in matters of marriage, Mehr (dower), maintenance divorce, khula Juridical separation, guardianship, gift, succession and aukaf, where parties are Muslims, the rule of decision shall be the Muslim Personal Law.